Epigenetic control and genomic imprinting dynamics of the Dlk1-Dio3 domain - Weinberg-Shukron, Ariella; Youngson, Neil A.; Ferguson-Smith, Anne C.; Edwards, Carol A. (Frontiers in Cell and Developmental Biology, 2023)
Genomic imprinting is an epigenetic process whereby genes are monoallelically expressed in a parent-oforigin specific manner. Imprinted genes are frequently found clustered in the genome, likely illustrating their need for both shared regulatory control and functional inter-dependence. The Dlk1-Dio3 domain is one of the largest imprinted clusters. Genes in this region are involved in development, behaviour, and postnatal metabolism: failure to correctly regulate the domain leads to Kagami-Ogata or Temple syndromes in humans. The region contains many of the hallmarks of other imprinted domains such as long non-coding RNAs and parental-origin specific CTCF binding. Recent studies have shown that the Dlk1-Dio3 domain is exquisitely regulated via a bipartite imprinting control region which functions differently on the two parental chromosomes to establish monoallelic expression. Furthermore, the Dlk1 gene displays a selective absence of imprinting in the neurogenic niche illustrating the need for precise dosage modulation of this domain in different tissues. Here we discuss how differential epigenetic marks laid down in the gametes cause a cascade of events that leads to imprinting in the region, how this mechanism is selectively switched off in the neurogenic niche and why studying this imprinted region has added a layer of sophistication to how we think about the hierarchical epigenetic control of genome function.